Critical assessment of smart calculation-based spectroscopy versus chemometric-assisted methods: Application to combined antibiotic formulations - Abdullatif, Hind Ali; Michael, Adel Magdy; Trabik, Yossra Ahmed; Ayad, Miriam Farid (European Journal of Chemistry, 2022)
This work describes a comparative study of two multivariate chemometric and univariate spectrophotometric methods for the determination of a ternary drug mixture containing oxytetracycline HCl, bromhexine HCl, and lidocaine HCl. All methods show high sensitivity and similar linearity range. Meanwhile, the chemometric method has the advantage of higher accuracy, higher specificity and better regression parameters. The two spectrophotometric methods are constant multiplication coupled with spectrum subtraction and successive ratio subtraction coupled with spectrum subtraction while the chemometric method used partial least square and principal component regression models. In addition, a spiking technique was used to increase the concentration of bromhexine HCl in the dosage form, allowing its determination despite its low contribution. Methods were successfully applied in the dosage form Oxyclear® veterinary injection in pure powder as well as in its pharmaceutical formulation. Statistical comparison showed no significant difference between the developed methods and the reference method.